Frieze Pattern on Shibori Fabric - Ratih Puspasari; Setyo Hartanto; Mohamad Gufron; Pradnyo Wijayanti; Mega Teguh Budiarto (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Mathematics and culture are two things that are closely related to the activities of daily human life. Because Mathematics is a form of culture that is integrated in all people's lives. This means that, in culture we can find various kinds of mathematical concepts called ethnomathematics. Shibori is a technique of manipulating cloth originating from Japan, to create patterns through a dyeing method that has been around since the 8th century. The patterns created in Shibori generally depict an asymmetrical shape. In the Shibori motif there are several mathematical elements, one of which is the Frieze Group pattern. The Frieze Group is a subgroup of a symmetry group that is constructed by translation in one direction. The Frieze pattern has 7 (seven) types of patterns consisting of isometric combinations and can be classified as cyclic or dihedral groups. This study is an ethnographic study, with exploration and documentation of Shibori. The data analysis technique chosen is interview, observation and documentation. The research subjects were Shibori fabric craftsmen in Tulungagung district, East Java. The purpose of this research is to further examine the cultural patterns of Shibori Traditional cloth into Frieze patterns, as a way to understand mathematics through culture. The results of the research conducted have shown that there are mathematical concepts (geometry) in the Shibori motif, namely the Frieze pattern F1, F2, F3, F5, F6, F7. Keywords: Group Frizes; Ethnomathematics; Shibori